Analytical validation of a high-sensitivity cardiac troponin T assay - Giannitsis, Evangelos; Kurz, Kerstin; Hallermayer, Klaus; Jarausch, Jochen; Jaffe, Allan S.; Katus, Hugo (Clinical chemistry, 2010)
Background: We report the development of a novel high-sensitivity cardiac troponin T (hs-cTnT) assay, a modification of the Roche fourth-generation cTnT assay, and validation of the analytical performance of this assay.Methods: Validation included testing of analytical sensitivity, specificity, interferences, and precision. We established the 99th percentile cutoff from healthy reference populations (n = 616). In addition, we studied differences in time to a positive result when using serial measurements of hs-cTnT vs cTnT in patients with a confirmed diagnosis of non-ST elevation myocardial infarction (non-STEMI).Results: The hs-cTnT assay had an analytical range from 3 to 10 000 ng/L. At the 99th percentile value of 13.5 ng/L, the CV was 9% using the Elecsys® 2010 analyzer. The assay was specific for cTnT without interferences from human cTnI or cTnC, skeletal muscle TnT, or hemoglobin concentrations up to 1000 mg/L, above which falsely lower values would be expected. When the assay was evaluated clinically, a hs-cTnT higher than the 99th percentile concentration identified a significantly higher number of patients with non-STEMI on presentation (45 vs 20 patients, P = 0.0004) compared with cTnT, and a final diagnosis of non-STEMI was made in 9 additional patients (55 vs 46 patients, P = 0.23) after serial sampling. Time to diagnosis was significantly shorter using hs-cTnT compared with cTnT [mean 71.5 (SD 108.7) min vs 246.9 (82.0) min, respectively; P < 0.01].Conclusions: The analytical performance of hs-cTnT complies with the ESC-ACCF-AHA-WHF Global Task Force recommendations for use in the diagnosis of MI.
Gesehen am 10.03.2023